Counsellor Use of the Adlerian-Dreikurs Approach with Parents in the School Setting1 - Van Hesterent, Frank (Canadian Journal of Counselling and Psychotherapy, 2012)
Involvement with parents constitutes an important dimension of the elementary school counsellor's role. It is suggested that the Adlerian-Dreikurs approach is very well suited to working with families in the school setting. The approach is described in terms of its underlying theory and the means by which it can be implemented by school counsellors. Certain advantages of using the approach in the schools are also discussed.